Moringa Leaf Extract as a Natural Material for Anemia Treatment: Literature Review - Syafrina Yuandry; Elsa Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Moringa (Moringa Oleifera Lamk) is a type of herbal plant with a good effect and role for the hematologic system in humans. Moringa plants are often used by people in various countries, one of which is Indonesia as a herbal plant which is believed to be used as medicine to treat various diseases. The potential of Moringa leaves as a medicinal plant gave rise to the idea to conduct a Literature review article. The purpose of conducting this literature review is to provide information to all readers about the various benefits of the Moringa plant, especially as a natural remedy for Anemia. The method used in this study is a literature review article. The literature used is published or perrish, (2010-2023). Based on the results of the literature review, 10 journals were obtained. Based on the results of the review article literature, it is known that the part most often used as medicine is the leaf part of the Moringa plant, where this plant can be used to treat anemia, as an anti-tumor, anti-inflammatory, anti-bacterial, anti-helmintic, antioxidant, hypotensive, and antipyretic.